TEACHING METHOD (Analysis of International Sciences, 2025)
Teaching and learning always related to each other. There are many types of teaching and ways to teach. A teaching method comprises the principles and methods used by teachers to enable student learning. These strategies are determined partly on subject matter to be taught and partly by the nature of the learner.